Comparative evaluation of valethamate bromide and hyoscine butyl bromide on cervical dilatation in water buffaloes after detorsion - YADAV, RISHIPAL; SINGH, GYAN; YADAV, POOJA; DANGI, PRADEEP; MAGOTRA, ANKIT; MALIK, RAKESH; BIDHAN, DEVENDER; SHARMA, MANEESH; KUMAR, SANDEEP; KUMAR, TARUN (The Indian Journal of Animal Sciences, 2023)
After detorsion, incomplete cervical dilatation is major cause of dystocia. The present study aimed to investigate the comparative efficacy of valethamate bromide and hyoscine butyl bromide on cervical dilation after detorsion and their effect on haematological and biochemical parameters of torsion detorted water buffaloes. A total of 18 buffaloes were selected for study which were divided into three groups of six animals each. After detorsion by Sharma’s Modified Schaffer’s method, animals with grade I and grade II cervix were selected for the study. Group I (control group) buffaloes were administered with dexamethasone (40 mg, I/M), cloprostenol (500 μg, I/M) and mifex (450 mL, slow I/V) after successful detorsion. Along with these drugs, in group II and group III, valethamate bromide (100 mg, I/M) and hyoscine butyl bromide (160 mg, I/M) were administered, respectively. The cervical dilation rate (CDR) of each group was calculated and compared. Blood samples were collected three times: before detorsion, after treatment and at parturition. Group III (2.17±0.07 cm/h) had significantly higher CDR followed by group II (1.39±0.21 cm/h), and control group (0.47±0.19 cm/h). Serum calcium levels were also elevated after treatment. Both drug combinations were found safe haematologically and biochemically.